Wallace Stevens : A Poet's Growth - Lensing, George S., 1943- (Book collections on Project MUSE., 1986)
In Wallace Stevens: A Poet's Growth, George S. Lensing examines Stevens' gradual emergence and development as a poet, tracing his life from his formative years in Pennsylvania to his careers as a lawyer for the Hartford Accident and Indemnity Company and as one of the major poets of the twentieth century. Lensing draws extensively upon previously unpublished material from the Stevens archive at the Huntington Library, which contains letters, early drafts of poems, and notebooks. Two notebooks,Schemata and From Pieces of Paper, are here reproduced in full. The study is divided into three sections. In the first, Lensing examines the years before the publication of Sevens' first volume of poetry, paying special attention to the forces that hindered and enhanced his progress toward modernity. In the second, we see Stevens in the exercise of his craft. Lensing discusses the influence of the Romantics on the verse Stevens wrote as an undergraduate at Harvard; his interest in Oriental art, Cubism, and Fauvism; his anticipation of Imagism; and his imitation of certain French Symbolists. Sources of the epigraphs to Stevens' poems are identified fully for the first time, suggesting the role of Stevens' vast reading upon his poetry. Also considered is Stevens' voluminous correspondence with people from all over the world, some of whom he never met personally. These letters helped rescue Stevens from the insularity of his business life and aided in the making of his poems. The final section treats the critical responses to Stevens' poetry by such people as Harriet Monroe, editor and founder of Poetry, who was the first important reader and publisher of his work. Attention is also given to Stevens' explications of his poems. Wallace Stevens: A Poet's Growth is a comprehensive examination of Stevens' live and work. This study provides abundant new material, which will be of value to scholars and to those readers who are drawn to Stevens' poetry.